Surface area-dependent second harmonic generation from silver nanorods. Issue 33 (8th August 2016) - Ngo, Hoang Minh; Luong, Thanh Tuyen; Ledoux-Rak, Isabelle
Abstract : We have evidenced strong first hyperpolarizabilities in silver nanorods (AgNRs) for the first time. The first hyperpolarizability β values linearly depend on the surface area of AgNRs. Abstract : The nonlinear optical (NLO) properties of metallic nanoparticles strongly depend on their size and shape. Metallic gold nanorods have already been widely investigated, but other noble metals could also be used for nanorod fabrication towards applications in photonics. Here we report on the synthesis and NLO characterization of silver nanorods (AgNRs) with controllable localized surface plasmon resonance. We have implemented an original, one-step and seedless synthesis method, based on a spontaneous particle growth technique in the presence of polyvinylpyrrolidone (PVP) as a capping agent. Colloidal solutions of AgNRs with various aspect ratios (5.0; 6.3; 7.5; 8.2 and 9.7) have been obtained and characterized using Harmonic light scattering (HLS) at 1064 nm, in order to investigate their quadratic NLO properties. From HLS experiments, we demonstrate that hyperpolarizability ( β ) values of AgNRs display a strong dependence on their surface area.